Analysis of the Density of Sea Cucumbers (Holothurians) based on the Type of Coral Cover in Karimunjawa Waters, Jawa Tengah - Bambang Sulardiono; Boedi Hendrarto (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2014)
Ecologically Karimunjawa waters dominated by the type of coral reef ecosystems and their associated, so that the biological diversity, beauty, and can provide backup germplasm. Thus, the territorial waters of Karimunjawa has a very high productivity rate, one of which is a resource of sea cucumbers ( holothurians ). Types of coral cover as a exogeneous factor in an area waters contribute to the stability of sea cucumber populations in habitat. With the different types of coral cover will give the effect of the presence of population dynamics in the habitat, which in this case is expressed as the density of sea cucumbers (ha-1). Therefore, to see how the conditions of the type of coral cover in Karimunjawa waters and how the relationship between the type of coral cover with a density of sea cucumbers, then this research be done. Furthermore, the results of this study can be used as a reference for resource management in the Karimunjawa waters of the sea cucumber. The purpose of this study to determine (a) the type of coral cover in Karimunjawa waters, (b) the relationship between the type of coral cover with a density of sea cucumbers.The results of the analysis provide information that density individual ha-1 of sea cucumbers at all stations observed ranged from 70.6-110.9 individuals ha-1. Overall stations observed, it was found that the types of abiotic coral cover dominated by dead coral algae (DCA) and sand coral (S). Types of coral cover between stations on the magnitude of the density of sea cucumbers were not significantly different. There are similarities types of relatively low coral cover of the station Mrican against 3 other stations, namely Small Menjangan station, Legon Goprak and Karang Gumuk station at 12.10%, while the percentage of the greatest similarity exists between a Menjangan Kecil station to station sand coral by 63.47%. Keywords : Density, sea cucumbers and coral cover